APLIKASI MESIN PENCACAH DAN FERMENTASI JERAMI DALAM PRODUKSI KOMPOS DI KECAMATAN SILO KABUPATEN JEMBER - Halimatus Sa’diyah; Alfian Futuhul Hadi; Bambang Herry Purnomo; Sudarko Sudarko (Asian Journal of Innovation and Entrepreneurship, 2015)
Farmers Group JokoTole and BaruMuncul are from Karangharjo Village, Silo subdistrict, Jember.  Both groups had the awareness to use organic fertilizers in farming. In fact, they make their own organic fertilizer in the form of compost, using a mixture of forage or leaves and cow dung. During the process of making compost, they encounter time inefficiency in the process of cutting the leaves and dried cow dung. It is because it is done conventionally using a dagger. The amount of compost produced is not sufficient for both farmer groups. Therefore, the application of compost thrasher (chopper) can increase the productivity and also saves time and energy for the process. In addition to the increase in the amount of compost produced, quality improvement is also needed by increasing the levels of macro nutrients in fertilizers, such as N, P, and K. This will be achieved by improving the nutrition of cattle feed, especially taken as a mixture of manure compost through hay fermentation technology. Nutritious fodder increased nutrients in the cow dung, and its utilization will also increase the nutrient content of the compost that is made. Keywords: trasher, silage, compost